THE LEVEL OF PRESERVATION OF LINGUOCULTURAL COMPOUNDS IN THE TRANSLATION OF UZBEK NOVELS - Ablakulova Iroda Kamolidinovna (Scholars Digest Publishing, 2025)
This article analyzes the level of preservation of linguocultural combinations in the process of translating Uzbek novels into foreign languages. The importance of reflecting national and cultural characteristics in the translation process, the cultural competence of the translator, and the equivalence of linguocultural elements are considered. The study examines the level of preservation of linguocultural combinations using the example of translations of Uzbek novels into English, Russian, and other languages.
Keywords: Translation, linguoculture, fiction, equivalence, cultural differentiation, Uzbek novels.